A personal leadership statement (2023)
The educational field is a big place where schools and people in charge need to awaken and realize that leadership empowerment is essential nowadays in our educational system. To achieve it, principals, schools, and teachers need to be open-minded and collaborative with the resources provided to change the perceptions and accept the challenge to be an empowered teacher leader. This paper focuses on and describes teacher leadership empowerment in the educational process. This course prepared all of us to perceive our qualities as leaders and how to use them for the community we belong to, this leadership statement stated the importance and advantages of leadership empowerment in schools.